FORCED DEGRADATION STUDIES AND RP-HPLC METHOD VALIDATION FOR THE DETERMINATION OF CERITINIB IN BULK AND ITS PHARMACEUTICAL DOSAGE FORM - Kapavarapu, Sureshbabu; Mopidevi, Nageswararao; Rambabu Chintala (Asian Journal of Pharmaceutical and Clinical Research, 2015)
A simple stability indicating reversed-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the determination of ceritinib present in pharmaceutical dosage forms. The reported RP-HPLC method utilizes a BDS C18 Column (150 mm Ã— 4.6 mm, 5 Î¼m) in an isocratic separation mode. The mobile phase consists of 0.01 N potassium dihydrogen orthophosphate (KH2 PO4) buffer and acetonitrile in the ratio 55:45 (%v/v). The pH was adjusted to 4.5 with dilute orthophosphoric acid and flow rate was maintained at 1.0 ml/minutes and elute was monitored by using the ultraviolet detector at 320 nm wavelength. The retention time of ceritinib was 2.539 minutes. The method was validated as per ICH guidelines with respect to specificity, accuracy, precision, linearity, limit of detection (LOD), limit of quantification (LOQ), robustness, and stability parameters. The LOD and LOQ values were 0.02 and 0.06 ppm, respectively. The linearity of the drug was in the range of 25-150 Î¼g/ml with correlation coefficient of 0.999. The percentage recoveries of the ceritinib drug was ranged from 98.46% to 99.97%. The optimized method was proved to be specific, robust, and accurate for the quality control of ceritinib in pharmaceutical preparations. The stability of the drug was examined under different stress conditions forcibly. The method was successfully applied for routine analysis of ceritinib in tablet dosage form. Keywords: Ceritinib, Reversed-phase high-performance liquid chromatography, Stability validation, Ultraviolet detection.